Spatial Arrangement of Disability Inclusive Mosques on Islamic Universities in Yogyakarta, Indonesia - M. Syafi'ie; Kamil Alfi Arifin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Universities are required to implement inclusive design. However, many universities have not yet implemented it, and Islamic universities are no exception. Starting from the perspective of Henri Lefebvre's theory of space, this research aims to look at the spatial arrangements for inclusive mosques for people with disabilities on Islamic universities in Yogyakarta, namely how the implementation of inclusive infrastructure facilities in their representational spaces, as well as elaborating the extent to which the ideal spirit of Islam as raḥmatan lil-'ālamīn encourages inclusive spatial practices. This type of research is categorized as non-doctrinal with a sociological and conceptual approach. This research concludes: First, Islamic universities in Yogyakarta do not have specific rules and policies related to spatial mosques that are inclusive of people with disabilities. Second, most of the mosques on Islamic universities in Yogyakarta have fulfilled some accessibility criteria but not up to optimal access (full access). Mosques on Islamic universities in Yogyakarta are at the partial access level. Although both are at the partial access level, each mosque on the Islamic university in Yogyakarta has certain notes. Mosques on the universities of Universitas Islam Negeri Sunan Kalijaga, Universitas Ahmad Dahlan and Universitas Nahdlatul Ulama are considered to have higher accessibility features compared to mosque at Universitas Islam Indonesia which appear to be filled with many obstacles. Third, the value of raḥmatan lil-'ālamīn in these Islamic universities does not seem to fully encourage inclusive spatial practices and instead shows discriminative architecture that results in socio-spatial injustice for people with disabilities.